The individual-institutional-opportunity nexus in entrepreneurship: Bridging perspectives in entrepreneurship and community and regional economic development - Michael W.-P. Fortunato; Theodore R. Alter (European Regional Science Association (ERSA), 2010)
New perspectives in entrepreneurship are emerging that view the concept of opportunity as central in the domain of entrepreneurship research. However, a robust understanding of how entrepreneurs and local institutions perceive opportunity in the community is still nascent in the empirical literature. We wish to contribute to the debate by presenting a testable empirical framework that views entrepreneurship in the community primarily as embedded within individual entrepreneurs, local institutions, and perceptions about local opportunity. A better understanding of this complex relationship may clarify why many local entrepreneurship assistance programs are developed in the absence of entrepreneur input, why many local entrepreneurs have little or no interaction with institutions in their community intended to help small businesspeople, and who entrepreneurs and local institutional leaders believe should be responsible for identifying and exploiting opportunity. The objective of this work is to identify differences in how individuals and entrepreneurs think about opportunity, and to develop strategies to bolster collaboration and opportunity exploitation within and between these groups in order to enhance local economic development through entrepreneurship. This paper presents the preliminary findings of face-to-face interviews and written surveys with entrepreneurs and community institutional leaders in three American states (Maine, Pennsylvania, and Wisconsin) about their views on entrepreneurship, opportunity enhancement, and local economic development. Results regarding the process of entrepreneurship and individual-institutional interaction are compared in high- and low-entrepreneurship areas to identify opportunity-oriented strategies that seem to be working at the local level. Finally, strategies are developed to overcome barriers between individual entrepreneurs and their institutional environment to enhance opportunity identification and exploitation.
Keywords: 330